Engineering bone-forming callus organoid implants in a xenogeneic-free differentiation medium - Decoene, Isaak; Herpelinck, Tim; Geris, Liesbet; Luyten, Frank P.; Papantoniou, Ioannis (Frontiers in Chemical Engineering, 2022)
The field of tissue engineering aspires to provide clinically relevant solutions for patients through the integration of developmental engineering principles with a bottom-up manufacturing approach. However, the manufacturing of cell-based advanced therapy medicinal products is hampered by protocol complexity, lack of non-invasive critical quality controls, and dependency on animal-derived components for tissue differentiation. We investigate a serum-free, chemically defined, xeno- and lipid-free chondrogenic differentiation medium to generate bone-forming callus organoids. Our results show an increase in microtissue homogeneity during prolonged differentiation and the high quality of in vivo bone-forming organoids. The low protein content of the culture media potentially allows for the monitoring of relevant secreted biomarkers as (critical) quality attributes. Together, we envisage that this xeno- and lipid-free chondrogenic medium is compatible with industrial scale-up and automation while facilitating the implementation of non-invasive imaging and the use of quality control parameters based on secreted biomarkers.